The Bride - Rowlands, Samuel; Potter, Alfred Claghorn, 1867-1940 (Salt Lake City, UT : Project Gutenberg, 2005)
"The Bride" by Samuel Rowlands is a poem written in the early 17th century, specifically around 1617. It is primarily a dialogue poem that explores themes related to marriage, virginity, and women's roles in society. Through the voices of various characters, it addresses the contrasting lifestyles and responsibilities of married women versus unmarried maidens, providing insight into the social dynamics of the time. The narrative unfolds in a dialogue form where the Bride advocates for the joys and virtues of marriage, challenging the hesitant maidens who express their preference for single life. In response, the maidens voice various concerns about fidelity and the nature of men. The poem references the legendary birth of Merlin to illustrate the consequences of pride and disempowerment through single life. Ultimately, the Bride articulates eight key duties of wives in nurturing harmonious marriages, emphasizing loyalty and partnership. While it may not reach great poetic heights, Rowlands' work offers a glimpse into the societal expectations and gender roles prevalent in the early 17th century. (This is an automatically generated summary.)
Release date is 2005-05-01
Produced by David Starner, Phil Petersen, and the Online Distributed Proofreading Team
Keywords: English poetry